PUBLIC PARTICIPATION IN REALIZING POLICY ACCOUNTABILITY COVID-19 PANDEMIC HANDLING AT YOGYAKARTA SPECIAL REGION - Ahdiyana, Marita; Ulifah, Nuri (Natapraja, 2021)
This study aims to describe community participation in realizing policy accountability for handling the covid-19 pandemic in the Special Region of Yogyakarta. The research design used was a descriptive study with a qualitative approach. Community participation was analyzed using a spectrum of five levels of participation. The results showed that community participation has manifested itself at every level of the spectrum of public participation. However, community participation is still limited to passive participation, where the community is only involved in policy implementation. At the information level, various information systems have been created to provide information, but not all of them can be accessed by the public. At consult level, various opinions from the community and stakeholders have received a good response and used as a consideration Governor. At the level of involvement, community has positioned as both a subject and an active participant in volunteering since the start of the pandemic. At the level of collaborate, collaboration has reached the stage of opening space for participation from various stakeholders.  Last at the empower level, it has been carried out through various efforts. starting from the RT, RW, and Village levels. However, there has been no coordinated effort and clear division of roles in implementing the collaboration and empowerment.